Men's knowledge, understanding and factors influencing their beliefs about male circumcision in rural communities in Northern KwaZulu-Natal, South Africa - Sengwayo, Sicelo F (Department of Public Health and Family Medicine, 2015)
Numerous studies have reported compelling evidence that medical male circumcision (MMC) reduces HIV acquisition in men. MMC is now recommended by the World Health Organization (WHO) and UNAIDS as part of HIV prevention strategies in countries with heterosexually-driven HIV epidemics. This research project assesses men's knowledge, understanding and factors influencing their beliefs about male circumcision in rural communities in Northern KwaZulu-Natal, South Africa. The study was conducted a year after the launch of a medical male circumcision programme by the KwaZulu-Natal Department of Health.